Effect of Soy Lecithin and Sodium Cholate Concentration on Characterization Pterostilbene Transfersomes - Nurmahliati, Haifa; Widodo, Ferri; Puspita, Oktavia Eka (Brawijaya University, 2020)
Inflammaging is a systemic inflammation caused by the aging process without any infection from the outside and it is a very high factor affecting the morbidity and mortality in the elderly. Pterostilbene contained in blueberries can prevent inflammation and oxidation. However, pterostilben has low water solubility and stability, so that to improve stability and acceptability is by making Pterostilbene Transfersome. Transfersome consisted of phospholipid in the form of phosphatidylcholine as a forming component of vesicles, surfactants as Edge activators, which increased transfersomeâ€™s flexibility. The composition of lecithin as phospholipid and surfactant was variable that effecting the optimization of Transferome. This study aimed to determine the effect of the ratio between soy lecithin as phospholipid and sodium cholate as surfactants to particle size. Comparison used was soybean lecithin 94%: 6% sodium cholate (F1); 95% soybeans: 5% sodium cholate (F2); and soybean 96%: 4% sodium cholate (F3). The prepared formulations were characterized for organleptic, pH, particle size analysis and potential zeta analysis. The characterized were statistically analyzed with SPSS One-way ANOVA followed by Post Hoc Turkey, and Paired T-Test. Transfersom had whitish-yellow color with clarity were cloudy and soya-flavored, the particle size were <400nm with pdi <0.5 and zeta potential values> -30 mV. Based on the results, optimum transfersome formulation was Â 95% soybeans: 5% cholic acid (F2).